EKOTEOLOGI AL-QUR’AN DAN HADIS DALAM MERESPONS KRISIS LINGKUNGAN GLOBAL (STUDI KASUS BENCANA BANJIR DI SUMATERA) - Fitriani; Muzakkir; Sulidar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study explores the contribution of Qur’anic and Hadith-based ecotheology as an ethical framework in responding to the global environmental crisis, focusing on the case study of the 2025 flood disaster in Sumatra. Employing a qualitative approach with hermeneutic methods for religious texts and case study analysis, the research examines key concepts such as mizan (balance of nature), khalifah fil-ardh (human responsibility as stewards of the earth), the prohibition of israf (wastefulness), and Hadith teachings on tree planting and water conservation as ongoing charity (sadaqah jariyah). Findings reveal that verses such as QS. Ar-Rum: 41 and QS. Al-A’raf: 56-58 portray environmental degradation as a consequence of human actions, while Prophetic Hadiths provide practical encouragement for ecosystem restoration. In the Sumatra flood case, triggered by deforestation, urbanization, and climate change, the disaster is interpreted as a manifestation of fasad fil-ardh, resulting in thousands of casualties and economic losses in the trillions of rupiah. Islamic ecotheology offers a holistic, spiritually grounded solution for mitigation and prevention, including reforestation campaigns and environmental education within Muslim communities. This research contributes theoretically to the development of Islamic ecotheology and provides practical recommendations for faith-based environmental policies in Indonesia to enhance resilience against the global climate crisis